Comparative study between evidence-based or problembased learning and conventional method to improve the clinical problem solving of the medical students - Darto Saharso; Erny Erny (Indonesian Pediatric Society, 2001)
The purpose of this study was to compare learning methods between the conventional and educational technology with evidence-based medicine and problem based learning methods, which is in accordance with the ability of clinical problem solving of medical students. This quasi-experimental study involed medical students at ninth semester, index of achievement ranging between 2.5–3 and worked at the Child Health Department of Dr Soetomo Hospital from January until December 2000. Data included performance of history taking, physical examination, summary, diagnosis, planning examination, therapy, complication, prognosis, pathophysiology and total score. All of variables were analyzed by using t test with p < 0.05 was considered to be significant. We found significant difference between the two groups in terms of history taking, building the summary; establishing diagnosis, planning further investigations, planning treatment, predicting complication, and describing the pathophysiology, and total scores, but did not see any difference physical examination t = 0.3 p > 0.05 and in predicting prognosis. We concluded that the use of educational technology with problem-based learning and evidence-based medicine methods significantly improve the problem clinic solving of the medical students.